A clinical observational study of intestinal stoma and their complication from a tertiary care center in India - Tushar Kanti Saradar,; Puja Ganguly,; Jorge Pal,; Gautam Ghosh,; Bikash Chandra Ghosh, (Asian Journal of Medical Sciences, 2023)
Background: The present study is designed to deal with an indication of various stoma surgery, type of stoma formed, and various ju=of General surgery, RG Kar Medical College and hospital, Kolkata, from June 2020 to May 2021 The study includes patients 12 years and <65 years of populations All data were collected in a prospective manner with a questionnaire and analyzed. Aims and Objectives: The aim of the study was to study various type of stoma and their indication and to identify the various complication encountered that occurs after the construction of intestinal stomas to assess the ways in which these complication can be minimized and managed in a better way. Materials and Methods: This was a prospective and observational study conducted in the Department of General Surgery, R.G.KAR Medical College and Hospital both the emergency and elective department. The study was approved by the Institutional Ethics Committee. Results: From the study, it was observed that among the study population, most were male 32 (80%) than female 8 (20%). There were two peak age group found to undergo stoma surgery most of which is 31–40 years consisting of 25 (27.5%) and 51–60 years consisting of 25 (27.5%). Most of the stoma surgery was found to be done in emergency 31 (77.5%) than in elective 9 (22.5%) setting. The most common cause of stoma formation was found to be hollow viscous perforation 12 (30%). Among the type of stoma ileostomy is more common than colostomy. Loop stoma formations are more common than end stoma and double barrel stoma. The most common complication following stoma surgery was found to be skin excoriation 30%. Conclusion: Stoma surgery was associated with a high rate of complication irrespective of the surgical expertise, surgical setup, and per operative planning resulting in higher morbidity. With meticulous dissection, post-operative stoma care, early detection, and management of complications, also patient education helps to achieve good outcomes following stoma surgery.